2017
DOI: 10.1016/j.nbd.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Reduced noradrenergic innervation of ventral midbrain dopaminergic cell groups and the subthalamic nucleus in MPTP-treated parkinsonian monkeys

Abstract: There is anatomical and functional evidence that ventral midbrain dopaminergic (DA) cell groups and the sub-thalamic nucleus (STN) receive noradrenergic innervation in rodents, but much less is known about these interactions in primates. Degeneration of NE neurons in the locus coeruleus (LC) and related brainstem NE cell groups is a well-established pathological feature of Parkinson’s disease (PD), but the development of such pathology in animal models of PD has been inconsistent across species and laboratorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 89 publications
(128 reference statements)
1
27
0
Order By: Relevance
“…Bilateral models of 6-OHDA show, however, more robust NA deficits in the cortex and striatum (Vieira et al, 2019). 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated monkeys exhibit clear noradrenergic damage, including LC cell loss, lower NA concentrations in several brain regions, and reduced noradrenergic innervation of the SNc and the subthalamic nucleus (Pifl et al, 1991;Masilamoni et al, 2017). Some publications have also reported low NA striatal and cortical tissue content in MPTP mice (Luchtman et al, 2009;Nayyar et al, 2009;Ando et al, 2018).…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Bilateral models of 6-OHDA show, however, more robust NA deficits in the cortex and striatum (Vieira et al, 2019). 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated monkeys exhibit clear noradrenergic damage, including LC cell loss, lower NA concentrations in several brain regions, and reduced noradrenergic innervation of the SNc and the subthalamic nucleus (Pifl et al, 1991;Masilamoni et al, 2017). Some publications have also reported low NA striatal and cortical tissue content in MPTP mice (Luchtman et al, 2009;Nayyar et al, 2009;Ando et al, 2018).…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Further evidence for mitochondrial impairment in the pathogenesis of PD comes from the selective sensitivity of the substantia nigra and locus coeruleus to mitochondrial toxins, including 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), 6hydroxydopamine, rotenone and paraquat (Giannoccaro et al, 2017;Masilamoni et al, 2017). All are complex I inhibitors and administration causes neuronal death and gives rise to parkinsonism in animal models.…”
Section: Mitochondrial Impairment In Parkinson's Diseasementioning
confidence: 99%
“…Even more recently, NA innervation of the STN has been shown in primates, with convincing demonstration that the partial loss of NA innervation of the STN in monkeys rendered parkinsonian by chronic administration of 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP) could contribute to STN dysfunctions in PD (Masilamoni et al . ). In humans, it has also been suggested that the modulatory action of the NA system might be mediated by the STN‐cortical loops (Albares et al .…”
Section: Discussionmentioning
confidence: 97%